Some distinctive features of tax control in the contemporary business environment - Anđelković Mileva (Zbornik Radova Pravnog Fakulteta u Nišu, 2016)
Traditional tax control has proven to be an insufficiently effective means of verifying the overall real economic power of large taxpayers (multinational corporations and wealthy individuals). As compared to the increasing mobility of taxpayers, tax administration activities are limited by the territorial jurisdiction of the fiscal sovereignty. The crisis of public finances has forced many countries to focus on the prevention of tax evasion and aggressive tax planning, particularly in international tax matters. In this sense, the traditional forms of tax control are supplemented by some additional strategies which are to provide tax authorities with more data on tax payers' business operations, profit, income, expenses and property. In practice, some developed tax administrations already apply a number of specific measures: the disclosure of information about aggressive tax planning schemes, advance pricing agreement, advance tax rulings, the use of financial intermediaries in data exchange processes, improved taxation relations, automatic exchange of tax information, etc. These specific measures are intended to help tax administrations to overcome the discrepancy between the information at their disposal and the information held by the taxpayers, which facilitates a more realistic assessment of tax liabilities. This will ensure a better management of tax risk and better tax compliance, which will ultimately contribute to a more efficient development of tax systems in the contemporary global business environment.